2012
DOI: 10.1128/aem.00364-12
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Regulation of the Sequence-Specific mRNA Interferase Activity of MazF Fused to a MazE Fragment with a Linker Cleavable by Specific Proteases

Abstract: The genomes of human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) consist of single-stranded RNA encoding polyproteins, which are processed to individual functional proteins by virus-encoded specific proteases. These proteases have been used as targets for drug development. Here, instead of targeting these proteases to inhibit viral infection, we utilized the protease activity to activate a toxic protein to prevent viral infection. We engineered the MazE-MazF antitoxin-toxin system of Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…For example, we showed that induction of the mazF gene from an HIV-1 promoter leads to degradation of viral mRNAs [Chono et al, 2011;Okamoto et al, 2013]. Results from our laboratory and another group [Park et al, 2012;Shapira et al, 2012] showed that MazF can be used to create novel tools against HIV-1 and hepatitis C viruses. In the future, it is possible to utilize MazF and other bacterial endoribonucleases as tissue-specific and selective anti-cancer agents by using tissue-specific promoters and tissue-specific delivery systems.…”
Section: Discussionmentioning
confidence: 95%
“…For example, we showed that induction of the mazF gene from an HIV-1 promoter leads to degradation of viral mRNAs [Chono et al, 2011;Okamoto et al, 2013]. Results from our laboratory and another group [Park et al, 2012;Shapira et al, 2012] showed that MazF can be used to create novel tools against HIV-1 and hepatitis C viruses. In the future, it is possible to utilize MazF and other bacterial endoribonucleases as tissue-specific and selective anti-cancer agents by using tissue-specific promoters and tissue-specific delivery systems.…”
Section: Discussionmentioning
confidence: 95%
“…5b&d). The packaging cells were also protected by truncated forms of MazE (MazE42 and MazE61 [11] but not as well as wild type MazE and only cells expressing low levels of Gag-MazF-2NES were able to survive after puromycin selection (Fig. 5b, lanes 3,4).…”
Section: Resultsmentioning
confidence: 99%
“…The MazE or truncated MazE sequences (MazE42-GFP and MazE61E–GFP) [11] were amplified from pCold-MazE (a gift from Dr. Masayori Inouye, Rutgers-RWJMS) by PCR and subcloned into pSin-EF1α-GFP-ΔKpnI at the SpeI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MazEF is one of the most well-studied toxin–antitoxin (TA) systems and has been found on the chromosomes of many bacteria. The MazF protein has been recently categorized as an endoribonuclease [41,42] or as a type of RNA interference enzyme [43]. The link between this TA system and quorum sensing has also been explored recently through a small pentapeptide (NNWNN) called the Extracellular Death Factor (EDF) [44].…”
Section: Introductionmentioning
confidence: 99%